2016
DOI: 10.1186/s12890-016-0207-3
|View full text |Cite
|
Sign up to set email alerts
|

Mean pulmonary arterial pressure as a prognostic indicator in connective tissue disease associated with interstitial lung disease: a retrospective cohort study

Abstract: BackgroundPulmonary hypertension (PH) can develop in connective tissue disease associated interstitial lung disease (CTD-ILD), and contributes to increased morbidity and mortality. However, except for systemic sclerosis and mixed connective tissue disease, the impact of mean pulmonary arterial pressure (MPAP) on survival in CTD-ILD has not been sufficiently elucidated. We hypothesized that pulmonary arterial pressure may be a prognostic factor in CTD-ILDs regardless of the kind of CTD.MethodsWe evaluated the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
0
19
0
3
Order By: Relevance
“…Forty full‐text articles were assessed for eligibility (Figure 1). Fifteen (8 RHC and 7 echocardiography) studies were included in the meta‐analysis 2, 3, 4, 5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. The characteristics of the included studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty full‐text articles were assessed for eligibility (Figure 1). Fifteen (8 RHC and 7 echocardiography) studies were included in the meta‐analysis 2, 3, 4, 5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. The characteristics of the included studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Studies included in this analysis are Valerio et al,10 Heresi et al,11 Kovacs et al,5 Suzuki et al,12 Maron et al,3 Takahashi et al,13 Douschan et al,4 Assad et al,2 Abramson et al,14 Kjaergaard et al,15 Shalaby et al,16 Lam et al,17 Damy et al,18 Cabrita et al,19 and Choudhary et al 20. CI indicates confidence interval; M‐H, Mantel‐Haenszel; RHC, right heart catheterization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated mean pulmonary artery pressure (mPAP) is associated with a worse survival in a range of respiratory diseases including idiopathic pulmonary fibrosis (IPF) . The presence of pulmonary hypertension (PH), defined by mPAP ≥ 25 mm Hg at rest, is associated with a worse prognosis in IPF …”
Section: Introductionmentioning
confidence: 99%
“…Baughman et al [8] observed the worst survival in cases of PH due to lung disease, and much better prognosis in subjects with PH due to left heart failure, in the group of sarcoidosis patients. Takahashi et al [25] found mPAP to be a significant independent survival predictor in DPLD associated with CTD. Data obtained from PH registries indicate that prognosis of the patients with severe PH-DPLD is extremely poor, with only 20-30% of patients surviving 3 years [26,27].…”
Section: Prognosis Of Ph-dpld Patientsmentioning
confidence: 98%